ASSESSMENT OF THE LEVEL OF STUDENTS’ AWARENESS REGARDING THE SAFE USE OF DIGITAL TECHNOLOGIES IN THE CONDITIONS OF TRANSFORMATION OF THE EDUCATIONAL SPACE - Priadko, Nataliia; Liubchykova, Dariia (Physical and Mathematical Education, 2026)
Formulation of the problem. The modern educational process is undergoing an irreversible digital transformation, requiring students to have a high level of digital competence. A critical unresolved problem is the insufficient awareness among primary school students (in particular, 8th graders) about the safe use of information and communication technologies (ICT). Insufficient knowledge in personal data protection, cyber threat prevention, and digital negligence creates a high educational risk, hindering the successful implementation of national strategies for the digital transformation of education. This necessitates an empirical assessment of the target group’s actual level of awareness. Materials and methods. The study is based on an interdisciplinary approach, combining the concept of digital competence with the theory of educational risks. The empirical part was conducted at Chernihiv Lyceum No. 12, with 8th-grade students (N=77) surveyed during pedagogical practice. Methods of theoretical analysis and synthesis, as well as quantitative analysis with the calculation of descriptive statistical indicators, were used to assess the distribution of responses and the level of awareness of the components of digital security. The questionnaire was developed based on the security dimension of digital competence. Results. The study confirmed the high integration of digital technologies into the educational process (90.9% of students use digital technologies daily/several times a week) and an overall positive assessment of the tools (100% satisfaction). It was found that 37% of the surveyed students have insufficient knowledge and skills in the safe use of the Internet and in protecting their own data. It was found that 9.1% of students are not covered by targeted training for security issues. Infrastructure problems were also identified, in particular requests to improve Wi-Fi in protective structures, which are critical for ensuring the continuity and security of the educational process in wartime conditions. Conclusions. The study confirmed the problem’s relevance and indicated the need to shift the emphasis from technological integration to the formation of a security culture. The key conclusion is the need for the systematic integration of digital security and ethics as a cross-cutting theme across all curricula. The development of integrated training modules focused on practical skills to counter cyber threats and on strengthening the lyceum’s secure ICT infrastructure is recommended.